Implementasi Artificial Intelligence (AI) Dalam Pembentukan Peraturan Perundang-Undangan Di Indonesia - Nabila Fitri Amelia; Diva Maura Marcella; Hening Jiwa Semesta; Sabrina Budiarti; Saskiana Fitra Usman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Utilization of Artificial Intelligence (AI) in the formation of laws and regulations and its implications for ethics and security. This article highlights the limitations of AI in interpreting data and forming algorithms, which can lead to bias and discrimination. This article also discusses the role of legal experts in ensuring the ethical and safe use of AI within statutory regulations. The article provides examples of countries that have implemented AI in their legislation, such as Canada and the European Union. The article concludes that although AI has the potential to improve the efficiency, accuracy and quality of legislation, it should be used as a tool and not replace the role of lawmakers.